Translation As An Object Of Comparative Literature - Madaminova Mohimbonu Qahramonjon qizi (Genius Journals, 2025)
This article traces the development of translation theory from its origins in classical antiquity, through the Middle Ages and the Renaissance, to the modern era. It also examines key theoretical models, including transformational, semantic-semiotic, situational, and communicative approaches, and explores the dual linguistic and nonlinguistic aspects of translation.
Keywords: translation; early translations; comparative studies; lexical aspect